Dampak Sertifikasi Dan Pendidikan Terakhir Terhadap Kinerja Guru Paud Di Kabupaten Ponorogo - Nusa, Popila Rikma; Irawan, Edi (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2020)
Abstract: Certification allowance comes as a form of appreciation for professional teacher performance. However, the reality is that there are still many teachers who are not yet certified educators. This study aims to determine: 1) Is there a difference in the performance of PAUD teachers who are already certified and not certified; 2) Is there a difference in the performance of PAUD teachers with PAUD / Psychology and non PAUD / non Psychology education; 3) Is there an interaction between certification and recent education on the performance of PAUD teachers. This research uses a quantitative method with a comparative causal approach. with simple random sampling. Data analysis was performed using the two-way ANOVA test. The results of the study show that: 1) The performance of certified teachers is better than those not certified; 2) The performance of PAUD teachers with PAUD / Psychology and non PAUD / Psychology last education is equally good; 3) There is no interaction between certification and educational background on the performance of PAUD teachers.